Extracellular matrix protein anosmin‐1 modulates olfactory ensheathing cell maturation in chick olfactory bulb development. (4th July 2019) - Hu, Youli; Butts, Thomas; Poopalasundaram, Subathra; Graham, Anthony; Bouloux, Pierre‐Marc
Abstract: Olfactory ensheathing cells (OECs) are a specialized class of glia, wrapping around olfactory sensory axons that target the olfactory bulb (OB) and cross the peripheral nervous system/central nervous system boundary during development and continue to do so post‐natally. OEC subpopulations perform distinct subtype‐specific functions dependent on their maturity status. Disrupted OEC development is thought to be associated with abnormal OB morphogenesis, leading to anosmia, a defining characteristic of Kallmann syndrome. Hence, anosmin‐1 encoded by Kallmann syndrome gene ( KAL‐1 ) might modulate OEC differentiation/maturation in the OB. We performed in ovo electroporation of shRNA in the olfactory placode to knock‐down kal in chick embryos, resulting in abnormal OB morphogenesis and loss of olfactory sensory axonal innervation into OB. BLBP‐expressing OECs appeared to form a thinner and poorly organized outmost OB layer where SOX10 expressing OECs were completely absent with emergence of GFAP‐expressing OECs. Furthermore, in embryonic day 10 chick OB explant cultures, GFAP expression in OECs accumulating along the OB nerve layers was dramatically reduced by recombinant anosmin‐1. We then purified immature OECs from embryonic day 10 chick OB. These cells express GFAP after 7 days in vitro, exhibiting a multipolar morphology. Overexpression of chick anosmin, exogenous anosmin‐1 or FGF2 could inhibit GFAP expression with cells presenting elongated morphology, which was blocked by the FGF receptor inhibitor Su5402. These data demonstrate that anosmin‐1 functions via FGF signalling in regulating OEC maturation, thereby providing a permissive glial environment for axonal innervation into the OB during development. Abstract : Anosmin‐1 is associated with Kallmann syndrome characterized by olfactory bulb dysgenesis. Anosmin‐1 regulates olfactory enstheathing cell maturation via FGF signalling, providing a permissive glial environment for axon innervation in olfactory bulb.